The influencing factors of participation in time banking volunteer service for older adults among university students in Nanjing, China - Yue Wu; Siyu Liu; Yating Song; Zhirui Zhang; Yunlong Liu (Frontiers Media S.A., 2024)
ObjectiveThis study aims to identify factors influencing university students' participation in time banking volunteer services for older adults and provides evidence to promote the involvement.MethodsConducted in November 2022, we utilized a convenience sampling method to recruit students from the School of Aging Service and Management at Nanjing University of Chinese Medicine, China. Data was collected through an online questionnaire focusing on various aspects related to time banking volunteer services for older adults. Factor analysis was employed to extract variables, and logistic regression was applied to identify key determinants.ResultsA significant majority (82.67%) of participants expressed willingness to engage in volunteer services for older adults. Factor analysis uncovered six influential factors explaining 62.55% of the variance. Logistic regression highlighted four key determinants of students' willingness: value judgment (OR = 4.392, CI = 2.897-6.658), social support (OR = 1.262, CI = 0.938-1.975), social influence (OR = 1.777, CI = 1.598-3.799), and socioeconomic conditions (OR = 1.174, CI = 1.891-3.046).ConclusionTo foster sustainability and continuous time banking among university students majoring in aging service and management, a multifaceted support involving governmental, social, and university is recommended.